Complete mitochondrial genome of the mangrove killifish Kryptolebias hermaphroditus (Cyprinodontiformes, Rivulidae) - Kim, Hui-Su (Mitochondrial DNA B Resour, 2016)
The complete mitochondrial genome was sequenced from the mangrove killifish (Kryptolebias hermaphroditus). The genome sequence was 17,487 bp in size, and the gene order and contents were identical with those of the congeneric species (K. marmoratus) in the genus Kryptolebias with emphasis on the second control region (795 bp). Of 13 protein-coding genes (PGCs), 5 genes (ND2, CO2, CO3, ND3, and Cytb) had incomplete stop codons as shown in K. marmoratus. Furthermore, the stop codon of ND6 gene was AGG, while the start codon of CO1 gene was GTG. The base composition of K. hermaphroditus mitogenome showed an anti-G bias (13.45% and 8.19%) on the second and third position of the protein-coding genes (PCGs), respectively.